Outer Space Militarization and Normative Gaps in International Space Law: A Comparative Legal Analysis - Isnurwanto, Iwan; Birahayu, Dita; Ehirim, Ugochukwu Godspower (Jambura Law Review, 2026)
Disagreements between spacefaring states' strategic activities and the normative goals of international space law have persisted despite space's growing militarization. At the heart of this conflict is the fact that different legal understandings of the term "peaceful purposes" in the 1967 Outer Space Treaty have coexisted with growing military operations in orbit, due to the ambiguity of this term. This research takes a normative juridical stance, drawing on statutory, conceptual, and comparative methods to assess whether the current international legal system adequately addresses modern trends of space militarization. States are able to operationalize military space tactics without clear legal limitation, as the analysis shows that current legal instruments offer limited normative direction and lack effective enforcement mechanisms. The study looks for interpretive fragmentation and structural inadequacies in international space law by comparing state space doctrines and institutional reactions, instead of evaluating military results experimentally. The essay uses this legal analysis to provide prescriptive suggestions for improving normative clarity, such as limiting the testing of anti-satellite weapons, improving the operational definition of "peaceful use," and holding private actors more accountable under state oversight. This research does not assert empirical verification, but rather provides a normative legal assessment of the regulatory gaps that now exist and suggests reform strategies to strengthen space governance's consistency, transparency, and stability